2023
DOI: 10.1111/1756-185x.14568
|View full text |Cite
|
Sign up to set email alerts
|

Costovertebral joint involvement in radiographic axial spondyloarthritis: A case‐series computed tomography study

Abstract: Aims To evaluate structural changes of costovertebral joints (CVJ) in patients with radiographic axial spondyloarthritis (rAxSpA) using computed tomography (CT) studies. Methods Available chest or thoracic spine CT studies of 17 patients with rAxSpA and 17 patients with rheumatoid arthritis (RA) were analyzed. Ankylosis, erosions, joint space narrowing, and osteophytes were assessed. Results The groups were similar by patients' average age, but the rAxSpA group included more males (11/17) compared to the RA gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…However, the significantly higher CV scores in AS patients, and the CTr joint scores of the SpA group being higher than that of the RA and non‐rheumatic diseases group, may suggest that these joints are affected not only by age, but also by the inflammatory process. Research comparing CV and CTr joint alterations in AS and RA patients found that AS patients had higher structural changes, which is consistent with our findings 12 . Nevertheless, the percentage of men in the AS group was higher in both our study and the cited study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the significantly higher CV scores in AS patients, and the CTr joint scores of the SpA group being higher than that of the RA and non‐rheumatic diseases group, may suggest that these joints are affected not only by age, but also by the inflammatory process. Research comparing CV and CTr joint alterations in AS and RA patients found that AS patients had higher structural changes, which is consistent with our findings 12 . Nevertheless, the percentage of men in the AS group was higher in both our study and the cited study.…”
Section: Discussionsupporting
confidence: 92%
“…Research comparing CV and CTr joint alterations in AS and RA patients found that AS patients had higher structural changes, which is consistent with our findings. 12 Nevertheless, the percentage of men in the AS group was higher in both our study and the cited study. Considering that men have higher joint scores, more research is required to identify whether this effect is due to gender or disease group.…”
Section: Ta B L Econtrasting
confidence: 58%
See 2 more Smart Citations
“…Several publications in humans report the importance, incidence and medical and surgical treatments of these joints in their relationship with back pain. [27][28][29][30][31] The high prevalence of pathology (OA, periarticular osteolysis, cyst-like lesions and fragments) of the CTJs in all breeds is of interest. Although nothing can be said yet about the possible clinical relevance of these findings, the observation certainly challenges the single focus on the APJs thus far in horses and warrants further research into these up to now overlooked joints.…”
Section: Discussionmentioning
confidence: 99%